2011 IEEE Symposium on Business, Engineering and Industrial Applications (ISBEIA) 2011
DOI: 10.1109/isbeia.2011.6088858
|View full text |Cite
|
Sign up to set email alerts
|

A review paper on fiber-optic sensors and application of PDMS materials for enhanced performance

Abstract: Fiber optic sensing technology is one of the fastest growing technologies in the modern day science. Optical fiber sensors draw more and more interests of researchers and application engineers for its exclusive and very valuable characteristics. It is mainly used to sense the physical and chemical properties such as micro-bending, strains, vibrations, accelerations, linear and rotary position, temperatures, pressures, determination of pH, refractive index of liquid solution, pipeline condition monitoring etc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In the traditional optical fiber sensing principle based on Mach-Zehnder interference, the light in the sensor can usually be divided into core-mode light (reference-mode light) and cladding-mode light (sensing mode light) [ 19 , 20 ]. The energy distribution of the light field can be analyzed according to the light intensity interference formula [ 20 , 21 , 22 , 23 ]: …”
Section: Sensors Coated With the Pdmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the traditional optical fiber sensing principle based on Mach-Zehnder interference, the light in the sensor can usually be divided into core-mode light (reference-mode light) and cladding-mode light (sensing mode light) [ 19 , 20 ]. The energy distribution of the light field can be analyzed according to the light intensity interference formula [ 20 , 21 , 22 , 23 ]: …”
Section: Sensors Coated With the Pdmsmentioning
confidence: 99%
“…This is the principle used in this part of the sensor. The performance of PDMS, which has a higher negative thermal optical coefficient (−4.66 × 10 −4 / • C) and thermal expansion coefficient (300 × 10 −6 / • C), has been fully reflected in the sensor [19].…”
Section: A Variety Of Structures Based On Mach-zehnder Interferencementioning
confidence: 99%
“…[1] Optical fiber sensors that have a very high bandwidth, electromagnetic interference of immunity and a strong capability of functioning under difficult environments of temperature, toxic and pressure. [2] In this field of optical fiber sensing technology, the fiber Bragg grating (Fiber Bragg Grating) sensors as an outstanding merit is one of the most exciting developments with multiplexing capability, and applied widely in various SHM paradigms. [3] An Fiber Bragg Grating has a special character to proceed and has been carried out as a sensor.…”
Section: Introductionmentioning
confidence: 99%
“…PDMS hydroxyl-terminated has been reported as a concrete additive [51] to reduce the production of calcite protecting the concrete structures against the reduction of the pH level. Sidek et al [52,53] reported the preparation of a fibre Bragg grating (FBG) sensor for strain detection in concrete structures, with and without a PDMS coating. PDMS coated FBG sensors have shown themselves to be more sensitive than uncoated FBG sensors [54].…”
Section: Introductionmentioning
confidence: 99%